Perancangan Pembangkit Listrik Tenaga Biogas Kotoran Sapi Di Desa Tanjung Baringin Simarulak Kabupaten Padang Lawas - ., Rimbawati; Harahap, Partaonan; Mangopo, Dultudes (Fakultas Teknik UMSU, 2025)
This study explores the feasibility of developing a Biogas Power Plant (PLTBg) utilizing cow manure as a renewable energy source in Tanjung Baringin Simarulak Village, Padang Lawas Regency, North Sumatra. The site, which hosts a government-managed cattle breeding center, generates a significant amount of organic waste that poses environmental challenges. Given the increasing demand for clean energy and the need to mitigate greenhouse gas emissions, biogas emerges as a promising alternative. The research adopts a descriptive approach with feasibility analysis, incorporating technical, financial, environmental, and social perspectives. Field observations and interviews with stakeholders, combined with secondary data, form the basis for evaluating project viability. The study estimates daily biogas production of approximately 75 m³ from 100 cows, which can generate around 120 kWh of electricity per day. Financial analysis shows a positive Net Present Value (NPV), an Internal Rate of Return (IRR) of 17.5%, a Profitability Index (PI) of 1.39, and a Payback Period (PBP) of 4.1 years.The findings indicate that the project is technically and economically feasible. It also offers environmental benefits by reducing methane emissions and turning waste into valuable energy and fertilizer. Socially, the project has the potential to reduce household energy costs and create new job opportunities in rural communities. Therefore, this biogas project is strongly recommended as a sustainable model for renewable energy development in Indonesia’s agricultural regions.